(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
Zoltán Kodály’s principles of music education are realised the best in Hungary in the music primary schools. The first music primary school was established by Márta Szentkirályi 1950 in Kecskemét. More and more music primary schools had been established in several cities of the country in the following years and decades. The new type of school required new type of music textbooks. Irma Bors, Márta Szentkirályi-Nemesszeghy and Helga Szabó-Párkai wrote the first music textbooks in the 1950’s. What was the image they conveyed about Kodály? Who was Kodály, the man, the composer, the collector of folksongs, the ethnomusicologist and the music pedagogue? Analysing these textbooks, I determined, that the first music textbooks outlined a Kodály-portrait, that faithfully presented Kodály, the man who offered his life to raise his nation’s musical culture and literacy to a higher level.